2021
DOI: 10.1128/msystems.00016-21
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Antiviral Innate Immunity by Avibirnavirus VP3 via Blocking TBK1-TRAF3 Complex Formation and IRF3 Activation

Abstract: The host innate immune system develops various strategies to antagonize virus infection, and the pathogen subverts or evades host innate immunity for self-replication. In the present study, we discovered that Avibirnavirus infectious bursal disease virus (IBDV) VP3 protein significantly inhibits MDA5-induced beta interferon (IFN-β) expression by blocking IRF3 activation. Binding domain mapping showed that the CC1 domain of VP3 and the residue lysine-155 of tumor necrosis factor receptor-associated factor 3 (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Beta interferon (IFN-β) was reported to play a critical role in inhibiting viral replication ( 49 ). IBDV dsRNA could be sensed by MDA5 (cytoplasmic RIG-I-like receptor melanoma differentiation gene 5) to induce IFN‐β expression ( 44 , 50 , 51 ). Therefore, we speculated that API5 might play an important role in regulating MDA5-induced IFN-β production.…”
Section: Resultsmentioning
confidence: 99%
“…Beta interferon (IFN-β) was reported to play a critical role in inhibiting viral replication ( 49 ). IBDV dsRNA could be sensed by MDA5 (cytoplasmic RIG-I-like receptor melanoma differentiation gene 5) to induce IFN‐β expression ( 44 , 50 , 51 ). Therefore, we speculated that API5 might play an important role in regulating MDA5-induced IFN-β production.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, TRAF3 is identified as the crucial adaptor protein for bridging TBK1 to upstream or downstream signaling complexes. 37,38 Binding of viral RNA or DNA to these receptors initiates downstream TRAF3-TBK1-IRF3 signal transduction, thus ultimately resulting in the production of IFN-I, and finally eliminating the virus infection. 26,31 The K63-linked polyubiquitination of TRAF3-TBK1 on several sites (such as K429/K436, Cys56, or Cys124) promotes an antiviral response, 39,40 but TRAF3 is also involved in DTX4-mediated K48-linked ubiquitination of TBK1 on K372, thereby promoting degradation of TBK1.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, TRAF3 is identified as the crucial adaptor protein for bridging TBK1 to upstream or downstream signaling complexes 37,38 . Binding of viral RNA or DNA to these receptors initiates downstream TRAF3–TBK1–IRF3 signal transduction, thus ultimately resulting in the production of IFN‐I, and finally eliminating the virus infection 26,31 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intervening the recognition of viral dsRNA genome by chMDA5, IBDV also employs other strategies to escape the innate immune response. It was reported that VP3 blocked the formation of TRAF3-TBK1 complex by reducing K33-linked poly-ubiquitination of Lysine-155 on TRAF3, inhibiting the production of IFN-I and facilitating viral replication ( 51 ). Interestingly, our previous study indicated that VP3 could interact with chicken Ribosomal Protein L18 (chRPL18) and chicken double-stranded RNA-activated protein kinase (chPKR), which enhanced IFN-I expression and inhibited viral replication ( 52 ).…”
Section: Innate Immune Evasion By Infectious Bursal Disease Virus (Ibdv)mentioning
confidence: 99%